Reconstruction of Types of Sentencing in the Juvenile Justice System in Indonesia (Discussion Against the Criminal Position of Warning) - Nurini Aprilianda; Liza Agnesta Krisna (Universitas Negeri Gorontalo, 2023)
The Juvenile Criminal Justice System is implemented with the principle that detention and imprisonment for children is a last resort. One type of criminal sanction is a warning penalty, namely a light sentence that does not result in restrictions on children's freedom. The light crimes in question can certainly be imposed on light cases as well. However, in reality, warning criminal sanctions are placed as the main type of crime. This type of research is normative, namely reviewing and examining the norms in the JCJS Law. There are contradictory circumstances between the aim of avoiding children from court proceedings and the position of warning criminal sanctions as part of the main type of crime. There are no strict parameters for the terms or types of criminal acts that can be called minor crimes. Referring to the purpose of the JCJS Law, based on the category of crime, considering the conditions for the implementation of diversion, and interpreting the term